PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN AGROFORESTRI DI KESATUAN PENGELOLAAN HUTAN (KPH) GEDONG WANI - Irma Yeny; Murniati Murniati; Sri Suharti (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2020)
As an effort to resolve conflicts in the FMU Gedong Wani area, a forestry partnership was conducted with an agroforestry system. To find out the extent to which the partnership scheme is able to invite community participation, then this study was conducted. This study aims to 1) determine the characteristics of the research area, 2) learn the profile of partnership farmers, 3) identify the form and level of participation of farmers, 4) formulate management recommendations. Data collection was carried out through interviews based on questionnaires and direct observation. Respondents are members of forest farmer groups involved in the partnership scheme. Measurements of participation are done with cross tabulation, while Likert scale method is using to measure participation level. The data is analyzed descriptively which refers to Hurairah (2008) and Arnstein (1969). The study shows that there are three tangible forms of participation in the development of agroforestry, namely participation in the form of ideas, labor contributions, as well as social participation in the form of inter-community support as a sign of kinship in managing partnership land. The level of participation of Agro Forest Park Forest Farmer Group (FFG) is at the 6th level, namely partnership. At this level farmers are able to negotiate and engage in activities with its partner (FMU). With this position, farmers have more space and power to involve in decision-making process.However, farmers do not have space in managerial decision-making and managerial work. This is not in line with the forestry development paradigm that places the community as subjects in forest management.